Penerapan Metodologi Tozer Dalam Perencanaan Strategis Sistem Informasi Pada PT Telekomunikasi Indonesia Tbk Witel Bandung - Valentina Risky Budi Prawestri; Agustinus Fritz Wijaya (APTIKOM SUMSEL, 2020)
Strategic planning of information systems is one of the keys in achieving the target expected by an organization. With interviews, observations, and document studies, this study aims to 1) evaluate strategic planning based on strengths, weaknesses, opportunities and threats in improving quality at PT. Telekomunikasi Indonesia Tbk, Witel Bandung to find strategic information sisem 2) develop strategically using Tozer method with SWOT Analysis analysis (strength, weakness, opportunities, threats), Value Chain Porter, CSF Analysis (Critical Success Factor), McFarlan Grid's Portfolio Application Analysis, PEST Analysis. The final result of this research in the form of strategic planning recommendations of information systems will be useful to improve the information system in PT. Telecommunications Indonesia Tbk, Witel Bandung.